Limitation of Application of Sharia Principles in Sharia Economic Dispute Resolution in Religious Courts - Zaidah Nur Rosidah (Journal of Morality and Legal Culture, 2020)
This paper aims to find the basis for the philosophical rationality of applying sharia principles in resolving sharia economic disputes in religious courts as well as the prerequisites required by religious court judges to apply sharia principles in resolving sharia economic disputes. The type of research used is normative legal research to find philosophical rationality and the institutionalization of sharia principles in resolving sharia economic disputes. The approach used is a conceptual approach. Secondary data were collected through literature study. The research results obtained first, the philosophical rationality of the application of sharia principles in sharia economic dispute resolution in line with the first and third principles of Pancasila. Second, the institutionalization of sharia principles becomes effective if there are prerequisites that must be met, firstly enough information for judges to understand sharia principles, secondly the obstacles that come from the judges themselves who are still oriented towards the flow of legism / positivism will have an effect on providing legal basis and third the speed of instilling the institutionalization of sharia principles can be done through education and training organized by the Supreme Court for Religious Court judges.